The Influence of The Role of Parents, The Role of The Teacher and Learning Motivation on Learning Outcomes - Tarigan, Hudiman; Asmawi, Moch; Wenly, Ayu Purnama; Fachrezzy, Fahmy (Gladi : Jurnal Ilmu Keolahragaan, 2023)
This study aims to reveal the direct and indirect effects, as well as the simultaneous effect of exogenous variables on endogenous variables. The sample in the study was 94 students from all 5th grade students, totaling 5 classes and totaling 126 people. The research approach used in this study is an associative quantitative approach. The data analysis technique uses a path analysis approach (path analysis). The results showed that: 1) there was a direct influence of the role of parents on learning outcomes at SDN Ciracas 07 Pagi Jakarta, which was 23.72%, 2) There was a direct effect of the role of the teacher on learning motivation at SDN Ciracas 07 Pagi Jakarta, which was 83.54 %, 3) there is a direct effect of learning motivation on learning outcomes at SDN Ciracas 07 Pagi Jakarta is equal to 34.34%, 4) there is an influence of the role of parents that has a direct and significant effect on learning motivation at SDN Ciracas 07 Pagi Jakarta is equal to 20, 16%, 5) there is a direct and significant effect of the teacher's role on learning motivation at SDN Ciracas 07 Pagi Jakarta, which is 83.54%, 6) there is an indirect effect on the role of parents through learning motivation on learning outcomes at SDN Ciracas 07 Pagi Jakarta is significant, 7) there is an indirect effect of the teacher's role on physical education learning outcomes through learning motivation is significant